LncRNA HEIH regulates proliferation and apoptosis of lung cancer cells through miR-98-5p - JIANG Qing-feng, YU Yong-kui, CHENG Jin-hua, SHEN Si-ning, XING Wen-qun (Jichu yixue yu linchuang, 2020)
Objective To investigate the effect of lncRNA HEIH on proliferation and apoptosis of lung cancer cells and its mechanism. Methods Human lung epithelial cells BEAS-2B and lung cancer cell lines A549, A427, H1299 and TKB-1 were cultured, and the expression level of HEIH was detected by RT-qPCR. Si-HEIH and miR-98-5p mimics were transfected into A549 cells inorder to silence the expression of HEIH in A549 cells or over-expressing miR-98-5p. Then cell proliferation was detected by MTT assay, apoptosis was examined by flow cytometry, and the levels of CCND1, caspase-3, SHH, GLI-1, PTCH and SUFU proteins were measured by Western blot. The dual luciferase reporter gene assay verified the relationship between HEIH and miR-98-5p. Results Compared with the normal lung epithelial cells BEAS-2B, the levels of HEIH in lung cancer cell lines,A549, A427, H1299 and TKB-1 were significantly increased (P＜0.05). Among them,the level of HEIH in lung cancer celllines A549 was the highest. Therefore, A549 cells were selected as the research object in the subsequent experiments. Silencing HEIH expression or over-expression of miR-98-5p reduced the A value of A549 cells after 12, 48 or 72 hours(P＜0.05)(MTT assay), increased apoptosis rates (P＜0.05) and inhibited CCND1 protein expression(P＜0.05), and promoted caspase-3 protein expression (P＜0.05). Over-expression of miR-98-5p also inhibited the mRNA and protein expression of SHH and GLI-1 in A549 cells (P＜0.05), and promoted the mRNA and protein expression of PTCH and SUFU (P＜0.05). Over-expression of HEIH reversed the effect of over-expression of miR-98-5p on proliferation and apoptosis of A549 cells and mRNA and protein expression of SHH, GLI-1, PTCH and SUFU. Conclusions Silencing HEIH expression may inhibit the proliferation of lung cancer cells and promote apoptosis by targeting miR-98-5p through Hedgehog signaling pathway.